Theoretical analysis of the philosophy and practice of disciplined inquiry - Hutchins, Shaun D., author; De Miranda, Michael, advisor; Lynham, Susan, advisor; Wickens, Christopher, committee member; Clegg, Benjamin, committee member (Colorado State University. Libraries, 2015)
This dissertation theoretically examined the process of disciplined inquiry in the social sciences from its philosophical foundations to its extensions into practice. Key to conceptualization of disciplined inquiry were two regulative ideals: the commitment to the concepts that define the possibility of experience and the commitment to processes for combining the concepts of experience. The paradigm theory of Lincoln, Lynham, and Guba (e.g., Lincoln & Lynham, 2011; Lincoln, Lynham, & Guba, 2011) provided a sophisticated explanation of the possibility of experience that inquirers can commit to when engaging in disciplined inquires. Review of literature revealed an inadequacy in the state of theoretical understanding of processes for combining the concepts of experience. To develop a theoretical agenda of research for disciplined inquiry, the literature on paradigm theory and theory building was analyzed. A historical analysis of paradigm theory revealed milestones in more than 40 years of inquiry focused on conceptualization of the theory. A reverse engineering analysis theoretically examined paradigm theory and its milestones identified from the historical analysis for key features of the theoretical process. A revised conceptualization of disciplined inquiry was presented and a theoretical agenda for developing the underlying theoretical framework for the processes of combining the concepts of experience was outlined.
Keywords: knowledge; paradigms; inquiry; theory; methodology